CURRENCY SUBSTITUTION IN INDONESIA - Pratomo, Wahyu Ario; Wiyadi, Wiyadi (Universitas Muhammadiyah Surakarta, 2009)
This article describes the phenomenon of currency exchange when there is high inflationÂ in a countryor itâs referred to dollarization.Â The phenomenonof high inflation also occurredÂ in IndonesiaÂ in recent years whenÂ the economic crisis.Â This articleÂ tries to examineÂ whetherÂ thereÂ dollarization inÂ 1997Â untilÂ 2004.TheÂ resultsÂ showedÂ thatÂ there hasÂ beenÂ exchangeÂ of currency or dollarizationÂ is significantÂ whenÂ theÂ economic crisis and its aftermath.